Modern data mining algorithms in C++ and CUDA C : recent developments in feature extraction and selection algorithms for data science - Masters, Timothy (Apress L.P., 2020)
Discover a variety of data-mining algorithms that are useful for selecting small sets of important features from among unwieldy masses of candidates, or extracting useful features from measured variables. --